Manajemen Pembelajaran Di SMA Swasta Budisatrya Medan - Inom Nasution; Dinda Syafira; Sri Nur Jamilah Simanjuntak; Apta Hafiz Sampurno; Muhammad Rizki Ramadhani (JUPE : Jurnal Pendidikan Mandala, 2022)
This study aims to determine the management of learning in the private SMA Budi Satrya Medan, in the management of student learning at the SMA Budisatrya Medan. The method used in this study is a qualitative method with data collection methods using interviews, observation and documentation. From the data we obtained from the Practice of Introduction to Educational Fields (PPL) II at the Budisatrya Private High School Medan, it is known that learning management starts from the planning and implementation process in improving the quality of education and the role of the Principal is carried out as well as possible in order to achieve learning objectives in accordance with the vision and Budisatrya Private High School mission. So it can be concluded that the efforts of the Budisatrya Medan Private High School Learning Management are inseparable from the efforts made by all components of human resources in the school.